Respuesta :
(3x−2)(2x+3)=0
(3x−2)=0; x = 2/3
(2x+3)=0; x = -3/2
answer
x = -3/2 and x = 2/3
(3x−2)=0; x = 2/3
(2x+3)=0; x = -3/2
answer
x = -3/2 and x = 2/3
Hi again!
(3x -2)(2x +3) = 0
6x² + 5x - 6 = 0
Now we have to factor the left side
(3x -2)(2x +3) = 0
Set factors equal to 0
3x -2 =0 or 2x + 3 =0
3x = 0 + 2 or 2x= 0 -3
3x = 2 or 2x = -3
x = 2/3 or x =-3/2
I hope that helps!
(3x -2)(2x +3) = 0
6x² + 5x - 6 = 0
Now we have to factor the left side
(3x -2)(2x +3) = 0
Set factors equal to 0
3x -2 =0 or 2x + 3 =0
3x = 0 + 2 or 2x= 0 -3
3x = 2 or 2x = -3
x = 2/3 or x =-3/2
I hope that helps!